A Prospective Comparative Study in Skin Antiseptic Solutions for Posterior Spine Surgeries: Chlorhexidine-Gluconate Ethanol Versus Povidone-Iodine. Issue 7 (August 2018) - Yoshii, Toshitaka; Hirai, Takashi; Yamada, Tsuyoshi; Sakai, Kenichiro; Ushio, Shuta; Egawa, Satoru; Yuasa, Masato; Kato, Tsuyoshi; Inose, Hiroyuki; Kawabata, Shigenori; Okawa, Atsushi
Abstract : Study Design: This is a prospective comparative study. Objective: We evaluated the efficacy of 2 standard antiseptic solutions, chlorhexidine-gluconate (CHG) and povidone-iodine (PD-I), in eliminating bacterial pathogens from surgical sites in posterior spine surgeries. Summary of Background Data: Previous studies have shown that CHG is more effective for skin antisepsis than PD-I in joint surgeries. However, few studies have investigated the preoperative use of antiseptic solutions in spine surgery. Materials and Methods: A total of 190 patients who received posterior spine surgeries were included in this study. The patients were allocated to the group treated with 0.5% CHG in ethanol (N=98) or 10% PV-I (N=92). Sterile culture swabs were used to obtain samples from the skin area adjacent to the planned incision site before preparation, after preparation, and after wound closure. Results: No differences were found between the CHG-treated and the PD-I-treated groups in the patients' age, sex, disease status, surgical site, operating time, and intraoperative blood loss. Before surgical skin preparation, bacteria grew in the cultures of specimens of 83.7% of the patients; no significant difference was found between the 2 groups. The common organisms isolated from both the cervical and lumbar spine surgical sites were Staphylococcus sp., Corynebacterium sp., and Bacillus sp. After the skin preparation, there were no significant differences observed in the culture positive rate between the CHG (3.1%) and PD-I (5.1%) ( P =0.49) solutions. The culture positive rates became higher after wound closure (preop=4.2%, postop=8.4%; P =0.07). The positive rate after wound closure in the CHG-treated group (5.1%) was smaller than in the PD-I-treated group (14.1%) ( P =0.046). However, no difference was found in infection rates between the 2 groups. Conclusions: While CHG-ethanol and PD-I were equally effective at eliminating the bacterial flora from the surgical site, CHG-ethanol showed a more favorable long-lasting effect for skin antisepsis in posterior spine surgeries.